Reflecting Best Practice on Vietnam, How to Develop Indonesia's National Electric Car Strategy - Andika Mustaqim (JEJAK, 2025)
On May 14-17, 2024, the researcher had the opportunity to visit the factory and meet with the executive team of VinFast, Vietnam's national electric car. After a long discussion with Indonesian journalists and automotive content creators, the researcher concluded that Indonesia is far behind Vietnam in developing national electric cars. On that basis, the researcher want to conduct research to develop an electric car strategy from upstream to downstream. The research approach is qualitative with the travelouge method (Davey, 2023) and Design and Development Research (Richey & Klein, 2009, 2013) with direct observation data collection in Vietnam, interviews and studies of social media and mass media. The analysis and research procedures produced a design for developing a national electric car. The results of this study (1) require political will from the government and synergy with the private sector to realize electric cars; (2) it is necessary to build a solid electric car ecosystem from upstream to downstream; (3) encourage mutually beneficial investment schemes to attract domestic investors; (4) encourage gotong royong (mutual cooperation) in Indonesian society. The strategy model for developing electric cars in Indonesia is oriented towards rapid market development and sustainable industries by learning from successful concepts in Vietnam.